Implementasi Discovery Learning dalam Memecahkan Persoalan Fikih di Pesantren - Tri Ruwanto (Universitas Islam Tribakti Lirboyo Kediri, 2026)
Fiqh learning in Islamic boarding schools is often identified with conventional methods such as sorogan and bandongan which are teacher-centered. Although effective for the transmission of classical knowledge, this method sometimes makes students less responsive to dynamic contemporary fiqh issues. Discovery Learning is present as an alternative active learning model that encourages students to find their own concepts and solutions through independent research and text analysis processes. The purpose of this study is to describe the steps for implementing the Discovery Learning model in fiqh learning and to analyze its effectiveness in improving students' ability to solve fiqh problems. The research method for writing this work uses the Literature Study method. Research Results: The research findings show that the implementation of Discovery Learning is carried out through six main stages: Stimulation (providing waqi'iyyah problems), Problem Statement (problem identification), Data Collection (exploration of yellow books/references), Data Processing (legal analysis), Verification (validation of discussion results), Generalization (legal conclusions).